Respuesta :

[tex]\bf (\stackrel{x_1}{0}~,~\stackrel{y_1}{-2})\qquad (\stackrel{x_2}{6}~,~\stackrel{y_2}{0}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{0-(-2)}{6-0}\implies \cfrac{0+2}{6}\implies \cfrac{2}{6}\implies \cfrac{1}{3} \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-(-2)=\cfrac{1}{3}(x-0) \\\\\\ y+2=\cfrac{1}{3}x\implies y=\cfrac{1}{3}x-2[/tex]